2009
DOI: 10.1017/s0022215109005489
|View full text |Cite
|
Sign up to set email alerts
|

In vitroactivities of fluconazole, itraconazole and voriconazole against otomycotic fungal pathogens

Abstract: This study found that the most common otomycotic fungal pathogen was A fumigatus, and that voriconazole had more potent in vitro activity than itraconazole against all Aspergillus species as well as against C albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Antifungal susceptibility data indicate that there are no significant differences in the susceptibilities of A. niger and A. awamori to either of the antifungal tested (Table 2). All isolates were resistant to fluconazole; this is in agreement with previous findings 24 . On the other hand, all isolates were found to be highly susceptible to terbinafine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Antifungal susceptibility data indicate that there are no significant differences in the susceptibilities of A. niger and A. awamori to either of the antifungal tested (Table 2). All isolates were resistant to fluconazole; this is in agreement with previous findings 24 . On the other hand, all isolates were found to be highly susceptible to terbinafine.…”
Section: Discussionsupporting
confidence: 92%
“…All isolates were resistant to fluconazole; this is in agreement with previous findings. 24 On the other hand, all isolates were found to be highly susceptible to terbinafine. Previous studies also indicated that black aspergilli are relatively susceptible to this antifungal drug.…”
Section: Discussionmentioning
confidence: 96%
“…The most common fungi reported in these infections are species from the genus Aspergillus , frequently A. niger and A. fumigatus although other moulds have been implicated 28,31–33 …”
Section: Discussionmentioning
confidence: 99%
“…No pediatric randomized trial has assessed the outcome of cardiac and CNS infections treated with voriconazole. Some studies have reported the successful outcome of IA management with voriconazole in the pediatric age group ( 17 ). Our patient was successfully treated with combination therapy (i.e., surgery and IV liposomal amphotericin B followed by four weeks of oral voriconazole).…”
Section: Discussionmentioning
confidence: 99%